Nurses’ Knowledge toward Prevention of Pneumothorax at Intensive Care Unit in AL-Hussein Medical City Hospital in Holy Karbala/Iraq (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aims: The study aims at assess nurses knowledge towards Pneumothorax and determine the relationship ofthose knowledge with their demographic characteristics.Methodology: To investigate nurse information relevant to Pneumothorax at Intensive Care Unit, aquantitative descriptive analysis used to assess approach with questionnaire items is performed. Throughoutthe non-probability sampling method, a purposive random sample of (30) nurses is chosen. A constructedquestionnaire includes (socio-demographic data and knowledge questionnaire items), data was collectionthrough the use of a questionnaire and self report nurses. Through the application the descriptive statistic,data were analyzed.Results: According to the analysis mean, the findings indicate that the majority (96.7 %) of nurses werepoor knowledge. As well as, there were no significant relationship between nurses knowledge and theirdemographic characteristics at p-value more than 0.05.Conclusion: This research found knowledge in terms of Pneumothorax, nurses were poor knowledge. Moreyears of experience in training the staff in intensive care unit and provide the health resources and exploitingyoung energies of nurses which indeed helps to develop their knowledge.
Keywords: Knowledge, Nurses, Pneumothorax, Prevention, Intensive Care Unit.